Late Presentations of Congenital Diaphragmatic Hernia - Bhandari, B B; Basnet, R B (Journal of Nepal Health Research Council, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE NE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The occurrence of congenital diaphragmatic hernia in adults is rare and misleading even to experienced clinicians. In contrast to neonatal diaphragmatic hernias, most of the adult patients present with vague gastrointestinal and respiratory symptoms mimicking other diseases. Hence high index of suspicion is required. When a diagnosis is established, it must be promptly treated surgically in order to avoid complications such as strangulation or bowel perforation. We present two cases of diaphragmatic hernia which were being managed as pulmonary pathologies. Keywords: bochdalek hernia, morgagni hernia